Determination of ABO antibody titre and haemolysin test of group O whole blood used for exchanged transfusion in a teaching hospital (Bangladesh Journal of Medical Science, 2022)
Background: Group O blood donor is more readily available and is frequently used as a universal red cell donor and emergency O whole blood (EM O) for exchange transfusion in neonates. Sera from group O donors contains two separable haemolysin antibodies, anti-A and anti-B, and a cross-reacting antibody called anti-A, B (mostly IgG). The presence of haemolysins in the donors may lead to haemolysis in the recipients.Objectives: This study aims to determine the prevalence of anti-A and anti B haemolysins and titer among group O donors that we screened for emergency group O (EM O) whole bloodMethodology: A cross sectional study was done to determine the prevalence of anti-A and anti B haemolysin and titer among group O blood donors screened for EM O whole blood for exchange transfusion in neonates at a teaching hospital from January to December 2018. Samples of 350 voluntary group O regular donors were selected for ABO antibodies titration and haemolysin test using the conventional tube technique at room temperature. Donors were screened for titer of 1:50 and 1:100 only. ABO antibody titer of ≥1:100 was considered as a high titer and not suitable for exchange transfusion. Titer of ≤1:50 were labeled as EM O whole blood and will be suitable for exchange transfusion.Results: A total of 350 group O blood donors were screened for the anti A and anti B haemolysin and titer. The majority of blood group O donors were male (n=215, 61%) and were age from 18-30 years old (51%). Malay was the predominant group (83%). About 52.9% of the donors were low titer (≤1:50), and 47.1% were high titer (≥1:100). Low titer was seen predominantly among male donors (61.8%). The prevalence of haemolysins in group O donors was 5.4% (n=19). Anti A and anti B haemolysins were seen in 0.57% and 2.28% of the donors, respectively, while donors having both A and B haemolysins in their sera was 2.57%.Conclusion: Prevalence of anti-A and anti-B haemolysins were low among group O blood donors. However, a significant percentage of group O donors have high titer of anti-A or anti-B. Therefore, despite the labour intensiveness of haemolysis titration technique and the frequent transfusion of group O blood for exchange transfusion, there is the need to routinely screen our donors for haemolysins in order to identify those posing the greatest risk to recipients.Bangladesh Journal of Medical Science Vol. 21 No. 02 April’22 Page : 368-372